Fluxnet Product from Norunda - Jutta Holst; Fredrik Lagergren; Harry Lankreijer; Anders Lindroth; Meelis Molder; Ecosystem Thematic Centre (Integrated Carbon Observation System, 2022)
Subset of half-hourly Fluxes and Meteo measurements processed with the international standard FLUXNET procedure (ONEFlux suite) for fast plotting purposes. Full data available in the Archive product.
Swedish Research Council (SRC) co-financed ICOS Sweden under Grant number 2015-06020
Ecosystem Thematic Centre, Holst, J., Lagergren, F., Lankreijer, H., Lindroth, A., Molder, M. (2021). Fluxnet Product from Norunda, 2013-12-31–2020-12-31, FLUXNET, https://hdl.handle.net/11676/qwGaRkeqNlg1x7MUZlxseg2S
Keywords: Carbon Portal; Warm Winter 2020; carbon flux; pre-ICOS; time instant, UTC; time instant, UTC; time instant, local non-DST time; time instant, local non-DST time; air temperature; air temperature; incoming shortwave radiation; incoming shortwave radiation; latent heat flux; latent heat flux; sensible heat flux; sensible heat flux; net ecosystem exchange; net ecosystem exchange; vapour pressure deficit; vapour pressure deficit; ecosystem respiration; ecosystem respiration; gross primary CO2 production; gross primary CO2 production; quality flag (int); quality flag (int); incoming long-wave radiation, net radiometer; incoming long-wave radiation, net radiometer; quality flag; quality flag; precipitation (total); precipitation (total); atmospheric pressure; atmospheric pressure; wind speed; wind speed; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap